Analysis of the Compatibility of Blockchain and Bitcoin Technology in the Digital Financial System: A Legal and Islamic Economic Review of Financial Innovation in the Digital Era - Sami, Muhammad (Sinergi International Journal of Islamic Studies, 2025)
This study aims to critically examine the compatibility of Bitcoin and blockchain technology with Islamic economic and legal principles within the context of a rapidly evolving digital financial system. Employing a literature review method based on the PRISMA approach, this research analyzes five authoritative classical Islamic jurisprudence texts alongside 40 scholarly articles from credible academic sources. The primary focus lies in evaluating how these emerging technologies correspond with key Islamic financial values, particularly the prohibitions of riba (interest), gharar (excessive uncertainty), and maysir (speculation/gambling), while also exploring their potential for innovation in building a Shariah-compliant financial infrastructure. The findings demonstrate that while Bitcoin, due to its high volatility and speculative nature, poses significant concerns under Shariah principles mainly due to its proximity to elements of maysir and gharar blockchain technology itself offers considerable promise. As a decentralized and transparent ledger system, blockchain can enhance justice (‘adl), trust (amanah), and efficiency in Islamic financial transactions. It supports the reduction of transaction costs, improves transparency, and eliminates reliance on intermediaries aligning with core objectives of Islamic economic ethics. Furthermore, blockchain technology provides a foundation for innovative financial instruments that uphold Shariah compliance, such as asset-backed stablecoins, automated smart contracts for contracts like murabahah or mudarabah, and real-time Shariah audits. The study finds increasing institutional support across Southeast Asia and the Middle East, where Islamic finance authorities, governments, and fintech developers are actively working to embed blockchain into compliant financial ecosystems. In conclusion, although Bitcoin's speculative characteristics challenge its Shariah compliance, blockchain technology opens significant opportunities to innovate and strengthen Islamic digital finance. The realization of this potential depends on sustained collaboration among Shariah scholars, technologists, regulators, and financial institutions to ensure all developments are guided by the objectives of maqasid al-shariah. This research contributes to the ongoing discourse on how Islamic values can shape the future of ethical and inclusive financial technologies.